Ultra-Short Pulsed Laser Engineered Metal-Glass Nanocomposites - Stalmashonak, Andrei; Seifert, Gerhard; Abdolvand, Amin.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Glasses containing metallic nanoparticles exhibit very promising linear and nonlinear optical properties, mainly due to the surface plasmon resonances (SPRs) of the nanoparticles. The spectral position in the visible and near-infrared range and polarization dependence of the SPR are characteristically determined by the nanoparticles’ shapes. The focus of Ultra-Short Pulsed Laser Engineered Metal-Glass Nanocomposites is the interaction of intense ultra-short laser pulses with glass containing silver nanoparticles embedded in soda-lime glass, and nanostructural modifications in metal-glass nanocomposites induced by such laser pulses. In order to provide a comprehensive physical picture of the processes leading to laser-induced persistent shape transformation of the nanoparticles, series of experimental results investigating the dependences of laser assisted shape modifications of nanoparticles with laser pulse intensity, excitation wavelength, temperature are considered. In addition, the resulting local optical dichroism allows producing very flexibly polarizing optical (sub-) microstructures with well-specified optical properties. The achieved considerable progress towards technological application of this technique, in particular also for long-term optical data storage, is also discussed.
Introduction -- Optical Properties of Nanocomposites Containing Metal Nanoparticles -- Interaction of Ultra-Short Laser Pulses with Metal Nanoparticles Incorporated in Dielectric Media -- Effect of Pulse Intensity and Writing Density on Nanoparticle Shape -- "Off-Resonant" Excitation: Irradiation Wavelength Dependence -- The Effect of Temperature on the Laser-Induced Modifications of Ag Nanoparticles -- Ultra-Short Pulsed Laser Engineering of Metal-Glass Nanocomposites -- Conclusions.
Keywords: Lasers; Photonics; Optical materials; Electronic materials; Nanoscale science; Nanoscience; Nanostructures; Nanotechnology; Optics, Lasers, Photonics, Optical Devices; Optical and Electronic Materials; Nanoscale Science and Technology; Nanotechnology